a ) 0,4 ×(3,5×0,2+11,8)+41
b) 72,8:(2,9×1,3-2,17)-32,45
Răspunsuri la întrebare
Răspuns de
9
a )
0, 4 × ( 3, 5 × 0, 2 + 11, 8 ) + 41 =
0, 4 × ( 0, 7 + 11, 8 ) + 41 =
0, 4 × 12, 5 + 41 =
5 + 41 = 46
b )
72, 8 : ( 2, 9 × 1, 3 - 2, 17 ) - 32, 45 =
72, 8 : ( 3, 77 - 2, 17 ) - 32, 45 =
72, 8 : 1, 6 - 32, 45 =
45, 5 - 32, 45 = 13, 05
0, 4 × ( 3, 5 × 0, 2 + 11, 8 ) + 41 =
0, 4 × ( 0, 7 + 11, 8 ) + 41 =
0, 4 × 12, 5 + 41 =
5 + 41 = 46
b )
72, 8 : ( 2, 9 × 1, 3 - 2, 17 ) - 32, 45 =
72, 8 : ( 3, 77 - 2, 17 ) - 32, 45 =
72, 8 : 1, 6 - 32, 45 =
45, 5 - 32, 45 = 13, 05
Nicomela:
5 + 41 = 46 Corectează, te rog !
Răspuns de
2
Salut,
0, 4 × (3, 5 × 0, 2 + 11, 8) + 41 =
0, 4 × (0, 7 + 11, 8) + 41 =
0, 4 × 12, 5 + 41 =
5 + 41 =
45✔
_______________________________
72, 8 ÷ (2, 9 × 1, 3 - 2, 17) - 32, 45 =
72, 8 ÷ (3, 77 - 2, 17) - 32, 45 =
72, 8 ÷ 1, 6 - 32, 45 =
45, 5 - 32, 45 =
13, 05✔
Alte întrebări interesante
Limba română,
8 ani în urmă
Informatică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Franceza,
9 ani în urmă